Chứng minh rằng. a. (x + 1)(x – 1) = x2 – 1 b. (x – 1)(x2 +x + 1) = x3 – 1 05/08/2021 Bởi Eliza Chứng minh rằng. a. (x + 1)(x – 1) = x2 – 1 b. (x – 1)(x2 +x + 1) = x3 – 1
a) `(x+1)(x-1)` `= x²+x-x-1²` `= x²-1²=x²-1`(đpcm) b) `(x-1)(x²+x+1)` `= x³-x²+x²-x+x-1²` `= x³-1²=x³-1`(đpcm) Bình luận
Đáp án: Giải thích các bước giải: a. `(x + 1)(x – 1)` `=x^2-x+x-1` `=x^2 – 1 ` (đpcm) b. `(x – 1)(x^2 +x + 1)` `=x^3+x^2+x-x^2-x-1` `= x^3 – 1` (đpcm) Bình luận
a) `(x+1)(x-1)`
`= x²+x-x-1²`
`= x²-1²=x²-1`(đpcm)
b) `(x-1)(x²+x+1)`
`= x³-x²+x²-x+x-1²`
`= x³-1²=x³-1`(đpcm)
Đáp án:
Giải thích các bước giải:
a. `(x + 1)(x – 1)`
`=x^2-x+x-1`
`=x^2 – 1 ` (đpcm)
b. `(x – 1)(x^2 +x + 1)`
`=x^3+x^2+x-x^2-x-1`
`= x^3 – 1` (đpcm)